2020
DOI: 10.3390/jcm9113635
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining Blood Glucose Levels in Range (70–150 mg/dL) is Difficult in COVID-19 Compared to Non-COVID-19 ICU Patients—A Retrospective Analysis

Abstract: Beta cell dysfunction is suggested in patients with COVID-19 infections. Poor glycemic control in ICU is associated with poor patient outcomes. This is a single center, retrospective analysis of 562 patients in an intensive care unit from 1 March to 30 April 2020. We review the time in range (70–150 mg/dL) spent by critically ill COVID-19 patients and non-COVID-19 patients, along with the daily insulin use. Ninety-three in the COVID-19 cohort and 469 in the non-COVID-19 cohort were compared for percentage of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 42 publications
(25 reference statements)
0
19
0
Order By: Relevance
“…Our findings are complementary to a recent analysis that examined time in target glucose range in patients admitted to ICU with COVID‐19. The authors found that ventilator use, neuromuscular blockade and use of high‐flow nasal oxygen all predicted poor glycaemic control 8 . Interestingly, this study compared glycaemia and insulin requirements in 93 COVID‐19 patients to all ( N = 469) contemporaneous ICU admissions (for any reason) without COVID‐19 and found that COVID‐19 patients had poorer glycaemic control and higher insulin requirements.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Our findings are complementary to a recent analysis that examined time in target glucose range in patients admitted to ICU with COVID‐19. The authors found that ventilator use, neuromuscular blockade and use of high‐flow nasal oxygen all predicted poor glycaemic control 8 . Interestingly, this study compared glycaemia and insulin requirements in 93 COVID‐19 patients to all ( N = 469) contemporaneous ICU admissions (for any reason) without COVID‐19 and found that COVID‐19 patients had poorer glycaemic control and higher insulin requirements.…”
Section: Discussionmentioning
confidence: 87%
“…The authors found that ventilator use, neuromuscular blockade and use of high-flow nasal oxygen all predicted poor glycaemic control. 8 Interestingly, this study compared glycaemia and insulin requirements in 93 COVID-19 patients to all (N = 469) contemporaneous ICU admissions (for any reason) without COVID-19 and found that COVID-19 patients had poorer glycaemic control and higher insulin requirements. However, the COVID-19 group required much more respiratory support compared to the non-COVID-19 group and the authors did not make any attempt to adjust for this difference.…”
Section: Diabetes Therapies Used In Patients With Covid-19 and Non-mentioning
confidence: 97%
“…44 In the same vein, a study on ICU patients showed that the less time spent in Open access range was associated with increased utilisation of a ventilator, prolonged mechanical ventilation and increased mortality. 45 Most importantly, a spline analysis of glucose levels in patients with DM with continuous glucose monitoring showed a non-linear relationship between time spent above range and glycaemic variability with the increased likelihood of composite adverse COVID-19 outcomes (need for ICU admission, mechanical ventilation or critical illness). 46…”
Section: Open Accessmentioning
confidence: 99%
“…This also prevented the analysis of time in range or BG variability, both being linked to increased severity, case fatality and poor COVID-19 outcomes. [42][43][44][45][46] Lastly, the study period coincides with the height of the first pandemic wave in Spain, when there was a shortage of ventilators and intensive care beds. At this point, age was the deciding factor for whether or not someone received potentially lifesaving ICU care.…”
Section: Limitations Of This Studymentioning
confidence: 99%
“…In the analysis of 562 ICU patients, the time in range (TIR) (70 -150 mg/dL) and the daily insulin dose in critical COVID-19 patients and non-COVID-19 patients were investigated [32]. The TIR in COVID-19 patients (44.4%) was significantly lower than non-COVID-19 patients (68.5%).…”
Section: Insulin Therapy In Glycemic Control Among Covid-19 Patientsmentioning
confidence: 99%